Pelatihan e-Faktur Sebagai Upaya Peningkatan Kompetensi Perpajakan Peserta Didik Lembaga Pendidikan Wearnes Malang - Yuniar Fitriyani (Politeknik Negeri Cilacap, 2023)
Tax experts are urgently needed since the Directorate General of Taxes has developed an information technology system to facilitate tax reporting, one of which is the e-Faktur application. The obstacle faced is the lack of prospective HR who are proficient in operating e-Faktur applications. Supporting the government program